Multipronged mapping to the dynamics of a barium atom deposited on argon clusters. Issue 47 (18th November 2016) - Awali, S.; Gaveau, M.-A.; Briant, M.; Mestdagh, J.-M.; Soep, B.; Gobert, O.; Maksimenka, R.; Poisson, L.
Abstract : Dynamics of an electronically excited Ba atom at the surface of an Ar≈500 cluster in a nanosecond frequency-resolved and femtosecond time-resolved multipronged approach. Abstract : The dynamics of an electronically excited barium atom deposited at the surface of an Ar≈500 cluster was explored in a multipronged approach which associates information from frequency-resolved nanosecond experiments and information from femtosecond time-resolved experiments. In both types of experiments, the dynamics is monitored by photoelectron and photoion spectroscopy.